STEM EDUCATION THROUGH PROJECT-BASED LEARNING - T Venkata Gopala Shastry; V Anand; M Shankar Lingam (International Journal of Advances in Business and Management Research (IJABMR), 2025)
This abstract examines the transformative role of project-based learning (PBL) in STEM education, focusing on how it nurtures critical thinking, creativity, and collaboration. By incorporating PBL technologies and interdisciplinary strategies, alongside a commitment to equity and inclusivity, PBL is shaping the future of STEM education. The research emphasises the broad impact of PBL, highlighting its potential to revolutionise how STEM subjects are taught and learnt. It stresses the importance of ongoing teacher training and professional development to address inclusivity and equity, as well as to integrate innovative PBL technologies for improving the quality of education. The abstract also calls for further research into the effectiveness of PBL assessment tools, a comparison with traditional teaching methods, and the long-term effects of PBL on student outcomes. Looking ahead, PBL will have an important impact on student learning experiences, fostering collaboration and innovation. With an emphasis on inclusive and interdisciplinary projects, PBL will ensure STEM education remains accessible and relevant, preparing a diverse, skilled workforce for the future.